A false positive finding in liquid chromatography/triple quadrupole mass spectrometry analysis by a non‐isobaric matrix component: the case of benzotriazole in urine for human biomonitoring. (8th June 2016) - Schlittenbauer, Linda; Seiwert, Bettina; Reemtsma, Thorsten
Abstract : Rationale: Multi‐residual methods employing liquid chromatography coupled to triple quadrupole mass spectrometry (LC/MS/MS) with selected reaction monitoring (SRM) are attractive also for human biomonitoring (HBM). A new process is determined that can lead to false positive findings by matrix components that are not isobaric to the analyte of interest. Methods: Benzotriazole (1H‐BT) was false positively detected in 87 human urine samples analyzed by ultra‐high‐performance‐(UHP)‐LC/MS/MS. The quantifier/qualifier ratio (Q/q ratio) did not match. This was further confirmed by negative results with an optimized gradient. Investigations were performed by UHPLC/high‐resolution (HR)MS and model compounds to reveal the identity of the disturbing matrix compound and the way that it interfered with 1H‐BT detection. Results: A formula of C7 H5 NO ( m / z 120.0444) was found at the retention time of 1H‐BT ( m / z 120.0556) belonging to an in‐source product ion of a heavier co‐eluting compound. Product ion spectra and Q/q ratios of model compounds indicated a benzene sub‐structure with a carbonyl and amine functional group in the ortho ‐ or para‐ position. Finally, folic acid was confirmed as the disturbing urine component, exhibiting an in‐source fragment with the nominal mass of 1H‐BT and the same product ions as used in the SRM mode for UHPLC/MS/MS monitoring. Conclusions: Interferences in SRM detection need not be due to co‐eluting isobaric matrix compounds, but can originate from in‐source fragmentation of heavier ions. Rigid quality control measures are recommended for LC/MS/MS analysis, especially for small molecules in complex sample matrices to overcome the selectivity limits of SRM. Copyright © 2016 John Wiley & Sons, Ltd.